The more you know, the less you fear: Reflexive social work practices in times of COVID-19. - López-Peláez, Antonio; Marcuello-Servós, Chaime; Castillo-de-Mesa, Joaquín; Almaguer-Calixto, Patricia (Sage, 2020)
In this article, we present the results of a strategy to disseminate best social work practices during periods of social lockdown in Spain, in a climate characterised by post-truth, misinformation and fake news. Social work is challenged with the task of delivering reliable and quality information aimed at building a better society. At the time of writing, Spain was one of the countries most affected by COVID-19, with one of the highest numbers of deaths per million inhabitants in the world. With the population in lockdown, our strategy was to design a series of innovative web seminars on both the subject and the procedures involved in social work, with the aim of sharing information and best practices to counter disinformation campaigns on social media. The results show the growing demand – both by citizens in general and students and professionals in particular – for reliable information in the field of professional practice. One of the priorities of digital social work must be to disseminate its results in the digital environment.
https://openpolicyfinder.jisc.ac.uk/publication/9224
Keywords: Trabajo social - Innovaciones tecnológicas; Noticias falsas; Confinamiento (Política sanitaria); Digital social work; Fake news; Lockdown